Dual‐Phase Aligned Composite Scaffolds Loaded with Tendon‐Derived Stem Cells for Achilles Tendon Repair. Issue 9 (19th July 2022) - Ning, Chao; Gao, Cangjian; Li, Pinxue; Fu, Liwei; Chen, Wei; Liao, Zhiyao; Xu, Zizheng; Yuan, Zhiguo; Guo, Weimin; Sui, Xiang; Liu, Shuyun; Guo, Quanyi
Abstract: Tendon injury is one of the most common musculoskeletal disorders, resulting in a significant decrease in the quality of life of patients with tendon injury. With the in‐depth understanding of the anatomical structure and pathological changes that occur during tendon repair, tissue engineering methods using cells and biomaterials are widely studied. However, simulation of the aligned tissue morphology present in natural tendons remains challenging. The design of a well‐aligned scaffold would be appealing to promote better tendon regeneration. Here, a dual‐aligned composite scaffold comprising an outer layer of polycaprolactone/silk fibroin (PCL/SF) copolymer electrospun membrane and an inner layer of tendon extracellular matrix (TECM) loaded with tendon‐derived stem cells (TDSCs) is developed to promote rabbit Achilles tendon repair. As resident, tissue‐specific cells, TDSCs possess stronger tenogenic differentiation abilities. The PCL/SF electrospun membrane with a dense structure provides mechanical support and TECM with a loose porous structure provides bioactive constituents and a microenvironment for tendon repair. As shown here, the engineered scaffold facilitates TDSC proliferation and migration, favors tenogenesis‐associated gene expression, promotes tendon repair with native‐like hierarchically organized collagen fibers, and enhances the mechanical properties, indicating its potential value in the tendon tissue engineering field. Abstract : A dual‐aligned composite scaffold comprising an outer layer of polycaprolactone/silk fibroin copolymer electrospun membrane and an inner layer of tendon extracellular matrix loaded with tendon‐derived stem cells to promote rabbit Achilles tendon repair are developed. An innovative strategy is provided here for future clinical applications in the tendon regeneration field.